1999
DOI: 10.1017/s0031182098003527
|View full text |Cite
|
Sign up to set email alerts
|

Scanning for nucleotide variations in mitochondrial DNA fragments of Schistosoma japonicum by single-strand conformation polymorphism

Abstract: In this study, we employed a mutation scanning approach for the direct visual display of genetic variability in mitochondrial DNA (mtDNA) fragments within and among populations of Schistosoma japonicum from the People's Republic of China. Fragments of the NADH dehydrogenase 1 gene (ND1) and the cytochrome c oxidase subunit I (COI) were individually amplified from parasite DNA by polymerase chain reaction (PCR), denatured and subjected to single-strand conformation polymorphism (SSCP) analysis. Using ND1 and CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

1999
1999
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 0 publications
0
22
1
Order By: Relevance
“…The enhanced display of sequence variation in ddF compared with, for example, SSCP and sequencing is largely the result of additional mobility shifts (i.e., SSCP components) and changes in band intensities following the dideoxy component(s) [8], and results in a higher mutation detection rate. For instance, a previous study (see [17]) demonstrated that SSCP was not always able to reliably differentiate samples (e.g., Sj4M1 and Sj4F10) differing by a point mutation in the ND1, whereas in this study, ddF allowed the sample Sj4M1 to be distinguished from SjF10 by the loss of a band at position 348 and a mobility shift as a consequence of the loss of a termination segment (see Fig. 1).…”
Section: Resultscontrasting
confidence: 59%
See 4 more Smart Citations
“…The enhanced display of sequence variation in ddF compared with, for example, SSCP and sequencing is largely the result of additional mobility shifts (i.e., SSCP components) and changes in band intensities following the dideoxy component(s) [8], and results in a higher mutation detection rate. For instance, a previous study (see [17]) demonstrated that SSCP was not always able to reliably differentiate samples (e.g., Sj4M1 and Sj4F10) differing by a point mutation in the ND1, whereas in this study, ddF allowed the sample Sj4M1 to be distinguished from SjF10 by the loss of a band at position 348 and a mobility shift as a consequence of the loss of a termination segment (see Fig. 1).…”
Section: Resultscontrasting
confidence: 59%
“…As expected, single nucelotide differences located toward the 3¢-end of the ND1 fragment (e.g., at nucleotide position 426; cf. [17]) were not detected as a consequence of the 5-terminal location of the primer binding site and the length of the fragment (404 bp). Nonetheless, if the detection or location of all nucleotide variations over the entire length of the ND1 fragment were required, then the current protocol could be readily adapted to incorporate 1±2 (internal) termination reaction primers, or by using bidirectional ddF [18].…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations